Hyper Spherical Search (HSS) Algorithm Based Optimization and Real-Time Stability Study of Tidal Energy Conversion System - Abhay Sanatan Satapathy; Asit Mohanty; Prakash K. Ray; Javed Khan Bhutto; Ahmad Jaber Mohammad Alfiafi; Omar Khulaif Alharbi (IEEE Access)
This article addresses the optimality and stability issues of a Tidal power based hybrid power system (HPS). The Tidal system gets destabilized by the uncertain variation of tidal waves and wind input. Stability of the system is restored through the introduction of Unified Power Flow Controller (UPFC) controller. The controller is optimized through the process of configuration of Hyper Spherical Search (HSS) based algorithm. The evaluation of the effectiveness of the suggested controllers is conducted through comparison analyses in order to regulate the voltage profile of the interconnected power network under various loading scenarios. The efficacy of the suggested controllers is assessed by stability analysis utilizing Eigen and Nyquist plots. Further, it is quite evident that optimal tuning is possible in case of the controller where the parameters can create significant impact on the system performance. Consequently, a novel heuristic optimization technique, such as HSS Algorithm are suggested to find the best output of the proposed controller. Finally, by using real-data, the performance as well as robustness of the suggested controller have examined by utilizing a real-time digital simulation platform, specifically the OPAL-RT 5142.